2016
DOI: 10.1038/ncomms13400
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of confined acoustic phonon polarization branches in free-standing semiconductor nanowires

Abstract: Similar to electron waves, the phonon states in semiconductors can undergo changes induced by external boundaries. However, despite strong scientific and practical importance, conclusive experimental evidence of confined acoustic phonon polarization branches in individual free-standing nanostructures is lacking. Here we report results of Brillouin—Mandelstam light scattering spectroscopy, which reveal multiple (up to ten) confined acoustic phonon polarization branches in GaAs nanowires with a diameter as large… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
73
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 60 publications
(131 reference statements)
6
73
0
Order By: Relevance
“…The propensity of simple elements to aggregate into clusters is observed at diverse length scales ranging from the sub-atomic level, where combinations of three quarks form baryons 1,2 , to the super-molecular level, where large macro-molecules are composed by smaller repeated units as in DNA 3 , proteins 4 , or synthetic plastics [5][6][7] , to the scale of the Universe, where thousands of stars congregate in galaxies 8,9 . In complex systems of a great multitude of components, cooperation among components and the emergence of collective phenomena yield unique properties that are not generally expressed by components of those systems taken in isolation [10][11][12][13] . Ferromagnetism 14,15 , phonon modes of an atomic lattice 16,17 , surface enhanced Raman spectroscopy 18,19 , superconductivity 20,21 , memory and cognitive functions of the brain 22,23 , depend less on the specialization of individual elements and more on the fact that these elements interact in long-range structures. These functions are thus scale dependent and generally break down at small cluster sizes [24][25][26][27] .…”
mentioning
confidence: 99%
“…The propensity of simple elements to aggregate into clusters is observed at diverse length scales ranging from the sub-atomic level, where combinations of three quarks form baryons 1,2 , to the super-molecular level, where large macro-molecules are composed by smaller repeated units as in DNA 3 , proteins 4 , or synthetic plastics [5][6][7] , to the scale of the Universe, where thousands of stars congregate in galaxies 8,9 . In complex systems of a great multitude of components, cooperation among components and the emergence of collective phenomena yield unique properties that are not generally expressed by components of those systems taken in isolation [10][11][12][13] . Ferromagnetism 14,15 , phonon modes of an atomic lattice 16,17 , surface enhanced Raman spectroscopy 18,19 , superconductivity 20,21 , memory and cognitive functions of the brain 22,23 , depend less on the specialization of individual elements and more on the fact that these elements interact in long-range structures. These functions are thus scale dependent and generally break down at small cluster sizes [24][25][26][27] .…”
mentioning
confidence: 99%
“…The phonon confinement effect has been argued in literature, some studies show that the confinement effect is only significant for low temperature, e.g., around and below 6.4 K for Si NWs with a diameter of 10.8 nm . While, other studies show that the phonon confinement occur even at room temperature …”
Section: D Nanostructures For Low Thermal Conductivitymentioning
confidence: 99%
“…Moreover, using the Brillouin light scattering, Graczykowski et al [50] studied mode propagation parallel and perpendicular to silicon strips on a silicon substrate, whereas Kargar et al [51] observed localized states in free-standing GaAs nanowires.…”
Section: Measurements Of Phononic Bandgaps and Phonon Dispersionmentioning
confidence: 99%